Analysis of Textual Composition and Its Pragmatic Functions: A Literary Investigation - Kudratov Laziz Farkhodovich; Jamaluddin Nasution (JALC : JOURNAL OF APPLIED LINGUISTIC AND STUDIES OF CULTURAL, 2025)
This study investigates the textual composition and its pragmatic functions within selected literary works, focusing on how language is structured and meaning is constructed in context. The phenomenon that motivates this research lies in the tendency of literary texts to be appreciated more for their aesthetic value than for their pragmatic dimensions, leaving a gap in understanding how such texts function communicatively in shaping interpretation. Previous studies, such as those by Austin (1962) on speech acts, Leech (1983) on pragmatic principles, and Rahardi (2009) on Indonesian pragmatic politeness, have highlighted the importance of pragmatic functions in discourse. However, limited attention has been given to their application in literary investigations, particularly in the Indonesian context. The problem addressed in this study is the insufficient exploration of pragmatic perspectives in analyzing textual composition in literature. This research employs a qualitative descriptive method, analyzing narrative data through pragmatic theories of speech acts, politeness, and implicature. The findings reveal that literary texts demonstrate multiple pragmatic functions, including directive, expressive, and representative acts, embedded within the narrative structure. These functions not only shape character interactions but also reflect cultural and social values conveyed through the text. The study concludes that textual composition in literature operates not only as an artistic arrangement of language but also as a communicative tool that guides readers toward deeper interpretation. The results are expected to contribute to broader discussions in applied linguistics, pragmatics, and literary studies, especially in integrating linguistic and cultural perspectives.